Bumpy moments: A potential method to uncover teachers’ beliefs in the context of Indonesia education - Elisabeth Desiana Mayasari; Tarsisius Sarkim (Journal of Psychology and Instruction, 2020)
Teachers’ belief is an element that influences teachers’ decisions in their activities in the classroom. Researchers have formulated theories to conceptualize teachers’ knowledge and a fundamental belief in their teaching and developed methods to unpack them. ’Bumpy moments’ has been indicated as a potential method to uncover teachers’ belief in their natural setting. This study aims at developing an understanding of primary school teachers’ beliefs which underlie their decision in their classroom setting. The research used bumpy moments as a method. One primary school teacher who participated in this research were videotaped while she was teaching. The researchers and teacher watched their recorded teaching and the teacher was interviewed by using unstructured interview protocol. The research question was answered by running qualitative research to the primary school teacher. The research demonstrated that there are teacher beliefs held by the teacher. This can be seen in 1) beliefs in experience and ability in using media and methods in teaching, 2) beliefs in good teaching skills because understanding the students 'emotional dynamics in class and understanding the students' thought processes in learning, 3) beliefs in experiences in learning pedagogical knowledge in teaching. Bumpy moments methods were a potential method to be developed in Indonesian contexts.